Multidimensionality of Modification in an Isopod-Acanthocephalan System - Park, Tracey; Sparkes, Timothy C. (Frontiers in Ecology and Evolution, 2017)
The acanthocephalan parasite Acanthocephalus dirus infects the freshwater isopod Caecidotea intermedius as an intermediate host before completing its life cycle in a fish. Transmission to the definitive host occurs after the parasite has reached the cystacanth stage and development into this stage is associated with changes in several behavioral and physiological traits of the host. Despite the numerous examples of trait modification in this system, little is known about the multidimensional nature of this modification. Here, we examined the relationships between cystacanth infection and expression of multiple traits (body color, refuge use, activity, and body size) of both male and female C. intermedius. The pattern of multidimensional modification was determined for males and females and then measures of behavioral plasticity, individual consistency and trait correlations were obtained for the modified traits. The results revealed that the overall pattern of host modification differed between males and females. Infected males and females showed similar decreases in body color but differed in changes to the other traits. Infected females were larger and less active than uninfected females, whereas infected males spent less time in refuge than uninfected males. A comparison between two situations revealed that refuge use exhibited high levels of plasticity and activity exhibited high levels of consistency and that these patterns differed based on both host sex and infection status. Analysis of the relationships among modified traits showed that traits appeared to be modified independently of each other and that correlations between traits that existed in one situation were absent in another. We suggest that the pattern of multidimensional modification is sex-specific and that the traits are modified independently. We also show that the patterns of multidimensional modification were not associated with variation in either parasite intensity of parasite size indicting that competitive interactions among parasites did not appear to act as a constraint on host modification.